Human-livestock diseases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Dr Kwenkam Paul of the Cameroon Ministry of Livestock, Fisheries and Animal Industries gives advice to livestock farmers on how to avoid the spread of infectious diseases, including those which can pass from animals to humans.